Impact of Le-Fort I osteotomy on anatomical and functional aspects of the nasal airway and on quality of life - Plath, Karim; Kühle, Reinald; Baumann, Ingo; Ristow, Oliver; Plath, Michaela; Freudlsperger, Christian (European archives of oto-rhino-laryngology and head & neck, 2019)
ObjectivesOrthognathic surgery is a well-established procedure for skeletal deformities. Beneficial influences to the posterior airway space (PAS) have been described, but little is known about the subjective aesthetical and functional nasal aspects after orthognathic surgery. The aim of this study was to evaluate nasal airflow by anterior rhinomanometry and volumetric changes in the nasal airway space after mono- or bimaxillary surgery using cone-beam computed tomography (CBCT) and a new segmentation software. Furthermore, changes of patient’s quality of life (QoL) should be assessed.MethodsTen patients (9 skeletal class malformation III, 1 skeletal class malformation I) were included. CBCT images, rhinological inspections and anterior rhinomanometries were performed before (T0) and after surgery (T1). All patients completed the FROI-17, the ROE and the SF-36 questionnaires.ResultsA significant postoperative gain for nasal airway volume compared with the baseline was shown (p < 0.014). No statistically significant differences between pre- and postoperative flow rates were found (p = 0.114). Pre- and postoperative cohorts did not differ in responses of disease-specific (ROE and FROI-17) and generic QoL questionnaires (SF-36).ConclusionMaxillary relocation surgery leads to a significant increase in nasal airway space. Subjectively, orthognathic patients did not experience any functional but psychosocial aspects after bimaxillary surgery.
Gesehen am 14.05.2019